Energy generation systems under unexpected operational conditions: consequences in view of components and consideration of resilience in the design phase - Silva, Fellipe Sartori da [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Energy systems are part of the critical infrastructures, and therefore any dysfunctionality can cause reactions in crucial societal fields. The more frequent and severe natural and man-made disasters increased the frequency of unexpected events, affecting these systems and exposing their vulnerability by leading them to abrupt disruptions. Resilience is a relatively recent concept in the thermal engineering field that is receiving attention due to the consideration of these high-impact, low-probability (HILP) events. This work aims to investigate the consequences of unexpected situations under these systems and establish a new method composed by seven quantitative metrics and a graphical analysis for resilience evaluation. The method was applied in four previously proposed cogeneration plants, two of them presenting redundancies. Both quantitative metrics and graphs converged to the same systems as the most and the least resilient ones, proving the robustness and reliability of the method. The inclusion of repairing actions hardly enhanced resilience of all the systems, mostly the less resilient ones, indicating that improving repairing conditions can be a great alternative to systems already in operation. The variation of input parameters revealed that operating time presents strong relation to resilience, indicating that systems projected to operate for shorter periods do not need significant investment in this field. Redundancy proved to be one of the important aspects for resilience evaluation, not being the major one under more detrimental scenarios, overcoming a possible initial idea that it is the main influence factor. Higher lifetimes provided extreme adverse environments, in which none of the configurations was able to continue its operation at an acceptable level. The graphical analysis pointed to the most resilient system as the one not only achieving more operating time, but also with highest energy generation along its lifetime. It also indicated that, for the analyzed scenarios, decreasing the failure rate could be more beneficial than invest in repair actions. In this evaluation, it became clear that the redundancy improved better the system availability, maintaining its operation for longer, compared to energy availability.

Sistemas de energia são parte das chamadas infraestruturas críticas e, portanto, qualquer alteração ou interrupção em sua operação pode ter alto impacto negativo em campos importantes da sociedade. Maiores frequência e intensidade de desastres naturais e antrópicos causaram um aumento de eventos inesperados, os quais afetam esses sistemas e expõem sua vulnerabilidade ao perturbá-los abruptamente durante sua operação. Por considerar essas situações extremas de baixa probabilidade de ocorrência e alto impacto operacional, o conceito de resiliência foi recentemente introduzido à engenharia térmica. O presente trabalho se propõe a investigar as consequências de situações inesperadas para sistemas de geração de energia, além de estabelecer um novo método de análise de resiliência, composto de sete métricas quantitativas e análise gráfica de parâmetros estabelecidos. O método foi aplicado em quatro plantas de cogeração previamente desenvolvidas, duas delas apresentando redundância. Tanto as métricas quantitativas quanto a análise gráfica convergiram para os mesmos sistemas mais e menos resilientes, provando a robustez e confiabilidade do método desenvolvido. A inclusão de ações de reparo aumentaram consideravelmente a resiliência de todos os sistemas, especialmente aqueles menos resilientes, indicando que melhorar as condições de reparo pode ser uma alternativa para plantas já em operação. A variação de parâmetros de entrada revelou que a vida útil esperada da planta apresenta forte relação com a resiliência, apontando que sistemas projetados para operar por curtos períodos não precisam de alto investimento nesse quesito. A redundância se destacou como um dos aspectos importantes para avaliação da resiliência, não sendo, entretanto, o principal sob condições adversas, fato que contraria uma possível ideia inicial de que esse é o fator de maior influência. Maiores tempos de vida útil criaram situações operacionais desfavoráveis, sob as quais nenhum sistema apresentou desempenho aceitável do ponto de vista prático. A análise gráfica apontou para o sistema mais resiliente como aquele não apenas que opera por maiores tempos, mas também que gera mais energia durante sua operação. Adicionalmente, ela também indicou que, para as condições simuladas, diminuir a taxa de falha pode ser mais benéfico que investir em ações de reparo. Por meio dessa análise, foi possível identificar que a redundância afeta de maneira mais acentuada a disponibilidade do sistema, mantendo sua operação por mais tempo, comparada à disponibilidade de energia.
Sistemas de geração de energia sob condições de operação inesperadas: consequências a nível de componentes e consideração da resiliência na fase de projeto
Keywords: Resilience; Energy system; Energy generation; Natural disaster; Man-made disaster; Graphical analysis; Resiliência; Sistemas de energia; Geração de energia; Desastres naturais; Desastres antrópicos; Análise gráfica; Sistemas de energia elétrica; Geração distribuída de energia elétrica; Energia - Fontes alternativas